2010
DOI: 10.1016/j.brat.2010.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Let it be: Accepting negative emotional experiences predicts decreased negative affect and depressive symptoms

Abstract: The present studies examined whether a tendency to accept negative emotional experiences buffers individuals from experiencing elevated negative affect during negative emotional situations (Study 1) and from developing depressive symptoms in the face of life stress (Study 2). Both studies examined female samples. This research expands on existing acceptance research in four ways. First, it examined whether acceptance has beneficial correlates when it matters most: in emotionally taxing (versus more neutral) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
108
3
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(130 citation statements)
references
References 70 publications
16
108
3
3
Order By: Relevance
“…In the ACE model, the emotion regulation skills of acceptance, tolerance, and modification of aversive emotions are assumed to be the most relevant for mental health, whereas the other emotion regulation skills are primarily included in the model because they are hypothesized to play a facilitating role in the successful application of the three aforementioned skills (Berking and Whitley, 2014). Our findings that awareness, acceptance, and tolerance mediated the effect of childhood trauma on subsequent depression match with previous conclusions on the relevance of these skills for the onset and maintenance of depression Radkovsky et al, 2014;Shallcross et al, 2010). The strong effect of the emotion regulation skill willingness to confront can be understood by a well-known mechanism.…”
Section: Discussionsupporting
confidence: 89%
“…In the ACE model, the emotion regulation skills of acceptance, tolerance, and modification of aversive emotions are assumed to be the most relevant for mental health, whereas the other emotion regulation skills are primarily included in the model because they are hypothesized to play a facilitating role in the successful application of the three aforementioned skills (Berking and Whitley, 2014). Our findings that awareness, acceptance, and tolerance mediated the effect of childhood trauma on subsequent depression match with previous conclusions on the relevance of these skills for the onset and maintenance of depression Radkovsky et al, 2014;Shallcross et al, 2010). The strong effect of the emotion regulation skill willingness to confront can be understood by a well-known mechanism.…”
Section: Discussionsupporting
confidence: 89%
“…These findings are consistent with a broader literature in which dispositional acceptance has been associated with reduced experiential avoidance [15][16][17], decreased negative affect, and reduced stress reactivity [60,61]. At the state level, brief mindfulness interventions have been linked to beneficial effects on stress and mood [24,35].…”
Section: Association Between Trait and State Measures Of Well-beingsupporting
confidence: 88%
“…Even though some evidence suggests potential short-term benefits (Wegner & Gold, 1995), the majority of studies examining the effects of experiential avoidance on subsequent negative affect found that avoidance backfires by increasing negative affect, especially in non-clinical samples. For example, students high in avoidance of negative affect reported higher negative affect when watching an aversive film clip compared to students low in avoidance (Shallcross et al, 2010, Study 1, see also Eifert & Heffner, 2003;Feldner et al, 2003, Levitt et al, 2004. Based on these results, we expected that the more students endorsed an entity view of emotion the more negative affect they would experience after an aversive event, potentially by using experiential avoidance throughout the aversive event.…”
Section: Implicit Theories Of Emotion Shape Regulation Of Negative Afmentioning
confidence: 95%
“…Avoiding negative affect, as we suspect entity theorists to do, leads to poor affective outcomes over time (Plump, Orsillo & Luterek, IMPLICIT THEORIES 5 2004;Shaar & Herr, 2011;Shallcross, Troy, Boland, & Mauss, 2010). For instance, the tendency to avoid negative affect-measured before a negative life event-predicts greater psychological distress after the negative life event as well as the subsequent development of depressive symptoms (Shallcross, Troy, Boland, & Mauss, 2010, Study 2;Shahar & Herr, 2011).…”
Section: Implicit Theories Of Emotion Shape Regulation Of Negative Afmentioning
confidence: 96%